PENGARUH KONSELING BEHAVIOR MENGGUNAKAN TEKNIK ROLE PLAYING TERHADAP SIKAP TANGGUNG JAWAB PADA SISWA KELAS VIII SMPN 1 PRAYA BARAT - Endriani, Ani; Patimarliza, Reza (Universitas Pendidikan Mandalika, 2021)
Abstract: Behavioral counseling using role playing technique is intended as a form of counseling activity that is focused on changing behavior by developing imagination and appreciation through role playing to increase students' attitudes of responsibility. The attitude of responsibility is an attitude in which a person has independence in learning, can complete learning tasks and obligations, is willing to bear all consequences or sanctions. The formulation of the problem in this research is